2007
DOI: 10.1111/j.1440-1746.2007.05049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects and probable mechanisms of electroacupuncture at the Zusanli point on upper gastrointestinal motility in rabbits

Abstract: Acupuncture may enhance the gastrointestinal myoelectrical activity of conscious rabbits. The cholinergic nerve, nitric oxide, motilin, and CCK may contribute to acupuncture mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…[42][43][44] In a previous canine study performed in our lab, EA was shown to improve gastric accommodation in vagotomized dogs, 15 suggesting nonvagal mechanisms. Niu et al 38 reported that effects of EA were mediated by cholinergic nerve, nitric oxide, motilin, and cholecystokinin. Yin et al 45 showed that effects of EA at ST-36 on gastric accommodation in diabetic rats were blocked by naloxone, suggesting an opioid mechanism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[42][43][44] In a previous canine study performed in our lab, EA was shown to improve gastric accommodation in vagotomized dogs, 15 suggesting nonvagal mechanisms. Niu et al 38 reported that effects of EA were mediated by cholinergic nerve, nitric oxide, motilin, and cholecystokinin. Yin et al 45 showed that effects of EA at ST-36 on gastric accommodation in diabetic rats were blocked by naloxone, suggesting an opioid mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…37 Similar effects of EA on gastric slow waves were also found in rats and rabbits. 14,38 In healthy human, EA at ST36 and PC6 decreased the percentage Transcutaneous electroacupuncture for gastric accommodation Z Huang et al…”
Section: Discussionmentioning
confidence: 99%
“…34 An animal experiment in a rabbit model demonstrated an increased number and amplitude of spikes of gastrointestinal myoelectrical activity, and a signifi cant increase in serum CCK concentrations from 5 min before to 1 h after acupuncture. 35 However, Lee et al showed contrasting fi ndings, with CCK levels increasing during electroacupuncture, but CCK levels 5 and 10 min after stimulation not differing signifi cantly from basal CCK levels. 34 In summary, some studies demonstrate increased CCK concentrations during acupuncture while others show that CCK increases some time after acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…EA at ST36 restored rectal distentioninduced impairment in gastric slow waves in dogs and increased the spikes in rabbits. [35][36][37] EA at ST36 improved the percentage of normal gastric slow waves as well as the percentage of tachygastria in healthy volunteers. 38 Liu et al 21 reported that 2-week TEA at ST36 decreased dyspepsia symptoms and elevated vagal activity in patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 99%